Cambridge igcse computer studies coursebook with cd-rom - Leadbetter, Chris; Wainwright, Stewart Stinchcombe, Alan (Cambridge University Press, 2011)
Fully covers the Cambridge IGCSE Computer Studies syllabus (0420), offering valuable practical support for students. Written by experienced teachers and examiners of Cambridge IGCSE Computer Studies, this highly illustrated coursebook covers both the theoretical and applied aspects of the course. It includes self-assessment questions and tasks throughout to reinforce learning. It offers clear learning objectives, chapter summaries and plenty of exam practice. The accompanying Student's CD-ROM provides guidance on study skills, revision and exam technique along with revision tests with answers, and exemplar exam answers. Now available in both print and e-book formats. The e-book includes both the print version and materials from the Student CD-ROM.